How to increase demand for carp? Consumer attitudes and preferences in Germany and Poland. Issue 11 (30th June 2020) - Zander, Katrin; Feucht, Yvonne
Abstract : Purpose: Carp is a traditional aquaculture fish with decreasing relevance in European markets. Despite this, it is a protein source which could contribute to the worldwide protein supply. Traditional carp ponds are part of human cultural heritage with high relevance for biodiversity. But, market shares of carp are small compared to other seafood market, mainly due to low consumer demand. The aim of this research was to contribute to the discussion on how to increase demand for carp by testing the acceptance of selected preprocessed carp products. Design/methodology/approach: A quantitative online survey was conducted in Germany and Poland with the aim of identifying consumers' attitudes towards carp and carp products. On this basis recommendations on how to best market carp products are developed. Findings: Carp is perceived to be a fish eaten primarily at Christmas and New Year's Eve and to be difficult to prepare. The analyses reveal that a potential for novel carp products does exist in Germany and in Poland. The wider introduction of a bonecut filet to the market, a better availability of carp products, and the avoidance of off-flavors are important prerequisites for higher market relevance of carp. Research limitations/implications: In this research consumer preferences were elicited "theoretically" by showing pictures of carp products and asking them for their preferences. In this regard, the results presented here state a general consumer interest and a potential for new carp products. Further research, integrating product tastings might give additional information on the likely success of new types of carp products. Practical implications: In order to let people know about the new products and at the same time to combat the sometimes existent bad image of carp, product tastings, also in combination with information regarding local origin and environmental/cultural impact, should be offered at the point of sale. Originality/value: Carp is a highly sustainable fish and offers a valuable protein source for human consumption. But, in its common ways of market presentation it is not highly appreciated by consumers. This paper demonstrates options of overcoming this situation.